1992
DOI: 10.1073/pnas.89.5.1856
|View full text |Cite
|
Sign up to set email alerts
|

Structural rearrangements of the chloroplast genome provide an important phylogenetic link in ferns.

Abstract: The chloroplast genome of most land plants is highly conserved. In contrast, physical and gene mapping studies have revealed a highly rearranged chloroplast genome in species representing four families of ferns. In all four, there has been a rare duplication of the psbA gene and the order of the psbA, 16S, and 23S rRNA genes has been inverted. Our analysis shows that the described rearrangement results from a minimum of two inversions within the inverted repeat. This chloroplast DNA structure provides unambigu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(32 citation statements)
references
References 23 publications
2
30
0
Order By: Relevance
“…(See also Hasebe et al 1993.) Studies on structural arrangements of the chloroplast genome in ferns (Stein et al 1992) support the latter finding. Rare duplications and gene orders show that genera like Adiantum and Dryopteris belong to the same lineage.…”
Section: Compatibility With Other Molecular Datasupporting
confidence: 66%
“…(See also Hasebe et al 1993.) Studies on structural arrangements of the chloroplast genome in ferns (Stein et al 1992) support the latter finding. Rare duplications and gene orders show that genera like Adiantum and Dryopteris belong to the same lineage.…”
Section: Compatibility With Other Molecular Datasupporting
confidence: 66%
“…The first of these was approximately 18 kb and the second was approximately 21 kb ). Mapping studies of Polystichum acrostichoides and Cyathea furfuracea, representative of two major branches within the core leptosporangiate ferns (sensu Pryer et al 2004), indicate they share the rearranged gene order found in A. capillus-veneris (Stein et al 1992;Raubeson and Stein 1995). This suggests the core leptosporangiates all have approximately the same gene order as A. capillusveneris.…”
Section: Introductionmentioning
confidence: 89%
“…changes in gene order, gene duplication and loss) are thought to be relatively rare. Plastid genome rearrangements have proved informative in many groups including embryophytes (Kelch et al 2004, Mishler & Kelch 2009), vascular plants (Raubeson & Jansen 1992), ferns (Stein et al 1992), Asteraceae (Jansen & Palmer 1987) and recently in mosses (Goffinet et al 2005(Goffinet et al , 2007; rearrangements in mitochondrial gene order have also provided supporting information for liverwort relationships inferred from DNA sequence data (e.g. Wahrmund et al 2008, Knoop 2010.…”
Section: Introductionmentioning
confidence: 99%